2011
DOI: 10.1073/pnas.1018974108
|View full text |Cite
|
Sign up to set email alerts
|

CD8 + T regulatory cells express the Ly49 Class I MHC receptor and are defective in autoimmune prone B6-Yaa mice

Abstract: The immune system includes a subpopulation of CD8 + T cells equipped to inhibit the expansion of follicular T helper (T FH ) cells, resulting in suppression of autoantibody production and associated lupus-like disease. These CD8 + T regulatory (Treg) cells recognize Qa-1/peptide complexes on target T FH cells and depend on the IL-15 cytokine for development and function. Here we show that these CD8+ Treg cells express a triad of surface receptors-CD44, CD122, and the class I MHC receptor Ly49-and account for <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
188
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(205 citation statements)
references
References 35 publications
17
188
0
Order By: Relevance
“…16,17 We have also found that CD8 1 CD122 1 T cells are memory-like Tregs that suppress allograft rejection in a murine model. 18 Hence, CD8 1 CD122 1 Tregs correspond to CD4 1 CD251 Tregs, given that CD122 is the b subunit of the IL-2 receptor on T cells, while CD25 is the a subunit of the same receptor, 19 which indicates that both subunits of the receptor are involved in Treg regulation.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…16,17 We have also found that CD8 1 CD122 1 T cells are memory-like Tregs that suppress allograft rejection in a murine model. 18 Hence, CD8 1 CD122 1 Tregs correspond to CD4 1 CD251 Tregs, given that CD122 is the b subunit of the IL-2 receptor on T cells, while CD25 is the a subunit of the same receptor, 19 which indicates that both subunits of the receptor are involved in Treg regulation.…”
Section: Introductionmentioning
confidence: 87%
“…14 The development of systemic lupus erythematosus-like disease in B6-Yaa mutant mice was associated with a defect in CD8 1 CD122 1 Treg cell activity, indicating that this Treg subset represents an effective therapeutic approach to systemic lupus erythematosus-like autoimmune disease. 16 Taken together, CD8 1 CD122 1 Tregs play an important role in the suppression or prevention of various autoimmune diseases in experimental animal models. Recent studies have also shown that CD8 1 CD122 1 Tregs play a regulatory role in alloimmunity as well as tumor immunity.…”
Section: Introductionmentioning
confidence: 99%
“…However, MHC‐E can also present some peptides derived from autoantigens and pathogens, which are recognized by CD8 + T cells. Qa‐1 is expressed at high levels on GC CXCR5 +  CD4 + cells, while CXCR5 −  CD4 + T cells express very low levels of Qa‐1; hence, Qa‐1‐restricted CXCR5 +  CD8 + T cells specifically target CXCR5 + Tfh cells 254. By mediating perforin‐dependent lysis of GC Tfh cells, they reduce the GC response and help to prevent autoantibody development 252, 254, 255.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…Qa‐1 is expressed at high levels on GC CXCR5 +  CD4 + cells, while CXCR5 −  CD4 + T cells express very low levels of Qa‐1; hence, Qa‐1‐restricted CXCR5 +  CD8 + T cells specifically target CXCR5 + Tfh cells 254. By mediating perforin‐dependent lysis of GC Tfh cells, they reduce the GC response and help to prevent autoantibody development 252, 254, 255. Although Qa‐1‐restricted CD8 + Treg cells express CXCR5, they do not express ICOS or PD‐1 or markers characteristic of CD4 + Treg cells such as FoxP3.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…Another important molecule involved in the action of CD8 + Tregs might be Qa-1, a nonclassical MHC class I molecule (MHC-Ib), as H. Cantor and his colleague found and reported a CD8 + T-cell subset that showed a regulatory activity under a Qa-1-restricted manner (30). In their recent publications, however, the Qa-1-restricted CD8 + Tregs they proposed were apparently shown to be CD122 + CD44 + (34,35). The Qa-1-restricted CD8 + Treg is overlapped with or involved in the CD8 +…”
Section: Cd122mentioning
confidence: 99%